“It’s just an issue and you deal with it… you just deal with it, you move on and you do it together.”: Men’s experiences of bacterial vaginosis and the acceptability of male partner treatment - Wigan, Rebecca (PLoS One, 2020)
Bacterial vaginosis (BV) is a common vaginal infection among women of reproductive age. Increasing evidence suggests BV may be sexually transmitted indicating a potential role for the treatment of sexual partners. If partner treatment reduces BV recurrence in women, real-world success will depend on sexual partners’ willingness to accept it. However, a lack of data exists on the acceptability of partner treatment among sexual partners, and no data exists on male partners’ experience of BV specifically. The aim of this study was to explore male partners’ views and experience of BV and their attitudes toward associated partner treatment. A social constructionist approach informed the framework of this study. Semi structured interviews were conducted with eleven men who participated in a BV partner treatment trial. Interviews were transcribed verbatim and analysed thematically. In the absence of symptoms in themselves, BV had little impact on men beyond their concerns for their partner’s health and self-esteem. Acceptance of treatment was largely a demonstration of care and support. While all participants had accepted treatment, men surmised the primary reasons other men may reject treatment as being: if they felt BV had “nothing to do with them”, which was related to not wanting to be viewed as having a ‘problem’ and exacerbated by norms of masculinity and STI-related stigma; lack of a diagnostic test to indicate if a male “had BV”; and a casual or less established relationship. Men’s attitudes to BV and partner treatment were primarily influenced by the nature of their relationships. The ambiguous aetiology of BV appears to attenuate STI related stigma and questions of infidelity.